That one spooky night - Bar-el, Dan (Kids Can Press, 2012)
Three strange tales filled with shivery fun occur on a dark, spooky night and include the stories of a broom that goes in search of a witch, mermaids who swim in a bathtub and a house party that turns unexpectedly batty.